2022
DOI: 10.29315/gm.v1i1.466
|View full text |Cite
|
Sign up to set email alerts
|

Há Mais “Vida” para Além da COVID-19

Abstract: A COVID-19 tornou-se a principal hipótese diagnóstica em muitas consultas. Este caso enaltece a necessidade de manter a abordagem holística, característica da Medicina Geral e Familiar. Mulher de 43 anos, com antecedentes de perturbação de ajustamento, fibromialgia e miomas uterinos, habitualmente medicada com: duloxetina; lorazepam; desogestrel. Foi avaliada numa “ADR-Comunidade” por cefaleias, náuseas, disgeusia, odinofagia, tosse, dispneia, mialgias e astenia, sem febre. Foi-lhe prescrito teste para COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…A significant increase in publications related to this group with the COVID-19 pandemic has been observed in all databases since the end of 2020. Despite the advances in scientific literature, we noticed gaps and divergences in some information, for example, related to vertical transmission during pregnancy, at the time of delivery or even the contagion of the virus from mother to newborn through breast milk, 6,[23][24][25] subjects that are not delimited and confirmed by science and instigate us to launch future research.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A significant increase in publications related to this group with the COVID-19 pandemic has been observed in all databases since the end of 2020. Despite the advances in scientific literature, we noticed gaps and divergences in some information, for example, related to vertical transmission during pregnancy, at the time of delivery or even the contagion of the virus from mother to newborn through breast milk, 6,[23][24][25] subjects that are not delimited and confirmed by science and instigate us to launch future research.…”
Section: Resultsmentioning
confidence: 99%
“…The levels of health care have been impacted by the COVID-19 pandemic due to the greater complexity involved in the pathology, demanding greater effort and overloading health professionals. 25,26 This new disease has gained prominence in the health-disease process, often diminishing the importance of other clinical diagnoses and treatments. Studies have shown that in the majority of situations in which an individual goes to the health unit, the professionals' actions are always directed towards the diagnosis and treatment of COVID-19 infection.…”
Section: Vulnerabilities and Impacts For Women In The Pregnancy Cycle...mentioning
confidence: 99%
See 3 more Smart Citations